1991
DOI: 10.1128/iai.59.6.1972-1977.1991
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides (Porphyromonas) gingivalis fimbriae activate mouse peritoneal macrophages and induce gene expression and production of interleukin-1

Abstract: The purpose of this study was to examine whether Bacteroides (Porphyromonas) gingivalis fimbriae, an important structure involved in attachment of the bacteria to periodontal tissues, activate macrophages and subsequently induce gene expression and production of interleukin-1 (IL-1) in the cells. The fimbriae increased glucose consumption and lysozyme activity in BALB/c macrophages, both criteria of macrophage activation of peritoneal macrophages, in a dose-dependent fashion. A marked increase in the mRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 36 publications
(43 reference statements)
0
63
0
Order By: Relevance
“…It has been previously demonstrated that P. gingivalis major fimbriae are able to induce expression of inflammatory cytokines in mouse peritoneal macrophages and that CD18 may play an important role in the associated signal transduction mechanisms [17,18]. Minor fimbriae of P. gingivalis (distinct from the fimA-encoded major fimbriae) have been demonstrated to induce proinflammatory cytokine release by THP1 cells and murine peritoneal macrophages in a CD14-and TLR2dependent manner [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that P. gingivalis major fimbriae are able to induce expression of inflammatory cytokines in mouse peritoneal macrophages and that CD18 may play an important role in the associated signal transduction mechanisms [17,18]. Minor fimbriae of P. gingivalis (distinct from the fimA-encoded major fimbriae) have been demonstrated to induce proinflammatory cytokine release by THP1 cells and murine peritoneal macrophages in a CD14-and TLR2dependent manner [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fimbriae are an important antigenic structure of P. gingivalis in periodontal disease because of their effect on host cells. Hanazawa et al (13,14) have reported that fimbriae of P. gingivalis induce production of interleukin-1 in mouse peritoneal macrophages and gene expression of the neutrophil chemotactic factor KC, which may contribute to infiltration of neutrophils into the periodontium of patients with adult periodontitis. Oral immunization of mice with P. gingivalis fimbriae induces increased levels of fimbria-specific salivary IgA and serum IgG antibodies, while subcutaneous immunization of the fimbriae results in elevated serum IgM followed by IgG responses (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…infiltrate (Stabholz & Sela 1983). Other potentially important bacterial virulence factors that are associated with increased production of cytokines, such as those under study in this investigation, include Fimbriae (Hanazawa et al . 1991) and lipoprotein (Radolf et al .…”
Section: Figurementioning
confidence: 99%